Research and Analysis of the Static Characteristics of Aerostatic Bearings with a Multihole Integrated Restrictor - Zhi-wei Lu; Jun-an Zhang; Bo Liu (Shock and Vibration)
In order to further study the performance of aerostatic bearing, an aerostatic bearing with a multihole integrated restrictor was proposed in this paper. Based on the physical model of aerostatic bearings, the governing equation was established, deduced discretely, and solved numerically by the finite-difference method and flow balance principle in Cartesian coordinates. The bearing capacity and stiffness of aerostatic bearings have been analyzed, and the relevant experimental research has been carried out in this paper. The results showed that the number of orifices in the integrated restrictor had a significant effect on the bearing capacity, and the maximum bearing capacity of a nine-hole integrated throttling bearing was approximately 1.9 times greater than that of a single-hole bearing. The bearing stiffness was greatly affected by the diameter of the orifices, and the optimum bearing stiffness was determined. The corresponding gas film clearance also changed accordingly.